Engineered NF-κB siRNA-encapsulating exosomes as a modality for therapy of skin lesions - Lu, Wei; Zhang, Jinzhong; Wu, Yungang; Sun, Wenxue; Jiang, Zipei; Luo, Xu (Frontiers in Immunology, 2023)
Despite the protection and management of skin has been paid more and more attention, effective countermeasures are still lacking for patients suffering from UV or chemotherapy with damaged skin. Recently, gene therapy by small interfering RNA (siRNA) has emerged as a new therapeutic strategy for skin lesions. However, siRNA therapy has not been applied to skin therapy due to lack of effective delivery vector. Here, we develop a synthetic biology strategy that integrates the exosomes with artificial genetic circuits to reprogram the adipose mesenchymal stem cell to express and assemble siRNAs into exosomes and facilitate in vivo delivery siRNAs for therapy of mouse models of skin lesions. Particularly, siRNA enriched exosomes (si-ADMSC-EXOs) could be directly taken up by the skin cells to inhibit the expression of skin injury related genes. When mice with skin lesions were smeared with si-ADMSC-EXOs, the repair of lesioned skin became faster and the expression of inflammatory cytokines were decreased. Overall, this study establishes a feasible therapeutic strategy for skin injury, which may offer an alternative to conventional biological therapies requiring two or more independent compounds.